Victors of the dry land - Attenborough, Richard, 1926-; British Broadcasting Corporation (Wilmette : Films Inc., 1981)
Naturalist Richard Attenborough describes the characteristics that made reptiles the first successful inhabitants of dry land and he shows the viewer examples of this ashtonishingly diverse family. Includes a discussion of the evolution of dinosaurs and the reasons for their sudden extiction.
Keywords: Reptiles; Reptiles -- Evolution; Dinosaurs